THE FINANCIAL HOMO IGNORANS OF THE HOUSEHOLD IN TÜRKIYE: DEMOGRAPHIC DETERMINANTS, FINANCIAL MANAGEMENT BEHAVIOR AND IMPACT ON FINANCIAL WELFARE (Third Sector Social Economic Review, 2024)
In today's economic systems, opposite of the other people, some people doesn’t prefer informed about these issues. The purpose of this study is to investigate whether significant relationship between the financial homo ignorance index (FHI) with the financial management behaviour, demographic variable and finanacial wellbeings of households in Turkey. In this study, it was found that there was a weak positive relationship between household FHI and gender, occupation, health insurance and financial management; while there is a weak negative relationship between the institution of employment, education level, mother's education level, and father's education level, and a moderate positive relationship between the household's FHI index and financial well-being; It was determined that there was a moderate negative relationship between age and monthly household income. In addition, there is a slight parallelism between the gender, profession, whether they have health insurance and the way they manage their income, and their financial illiteracy of the households participating in the research, and that women, in particular, prefer to be more ignorant about financial matters than men. Finally, the study in question revealed that people who postpone making decisions about financial management and don’t have health insurance are also slightly persistent in financial illiteracy.
Keywords: FHI Index; Financial Management Behaviour; Financial Wellbeing; DemographicVariables; Financial Homo Ignorans